Dimensions of Islamic Education in Shaping Students’ Character for 21st-Century Learning - Wenni Anggraini; Charles C; Muhammad Hizbi Islami (International Journal of Islamic Teaching and Learning, 2025)
Islamic education is an educational process grounded in the Quran, the Sunnah, the opinions of scholars, and the Islamic historical heritage. In the 21st century, education is required not only to equip students with knowledge but also to shape their character so that they are able to face global challenges. This article aims to examine the dimensions of Islamic education in shaping the character of 21st-century students. The study employs a descriptive-analytical method with a literature review approach, analysing relevant sources related to the dimensions of Islamic education and 21st-century learning. The findings show that Islamic education encompasses six main dimensions: physical, moral, intellectual, spiritual, aesthetic, and social. These six dimensions complement each other in shaping students who are faithful, knowledgeable, possess noble character, and demonstrate 21st-century skills such as critical thinking, creativity, communication, and collaboration. Thus, Islamic education plays a strategic role in preparing a generation that is not only academically competent but also characterized by Islamic values and equipped to face contemporary developments.